Posting What You Know and Caring for the Niche: How Micro-Influencers Survive Platform Culture Demands - Volpe, Camilla (Italian Sociological Review, 2026)
In recent years, platforms such as Instagram and TikTok have become central arenas for the performance of identity, consumption, and social values. Within this platformized ecosystem, second-hand fashion has emerged as a highly visible and narrativised content niche, particularly among micro-influencers. While second-hand consumption has long been linked to subcultural distinction and sustainability, its current digital mediation raises new questions about visibility, labour, and legitimacy. This article explores how micro-influencers represent and perform second-hand fashion on Instagram and TikTok and it investigates to what extent these practices reflect niche care and ethical commitment, or rather strategic acts of self-branding under platform pressures. Drawing on digital ethnography and semi-structured interviews, the study analyses how content creators navigate the demands of platform culture while attempting to professionalise their identities. Findings show that second-hand fashion is often selected not purely for ideological reasons, but because it is already familiar and easier to mobilise within the repetitive demands of content production, functioning as a sustainable and recognisable niche. These influencers present their work as a form of care and advocacy, yet such positioning simultaneously functions as reputational labour aimed at achieving visibility and legitimacy. Situated at the intersection of precarity, care, and professionalisation, these practices reveal how affective and ethical narratives are shaped and constrained by platform infrastructures. Rather than viewing these performances as inauthentic, the article argues for their interpretation as complex strategies of survival within the contemporary attention economy.